The Contribution Of Islamic Boarding Schools In The Formation Of Students' Character And Morals As Gen-Z - Mardani, Dadan; Susiawati, Iis (AIM: Journal of Islamic Education Management, 2024)
This article describes the role of Islamic boarding school in the character and moral education of students, with the type of literature research, in this study Islamic boarding school can play a role in the formation of student character supported by the main elements of Islamic boarding school, namely, teachers. Because all of that is inseparable from the role of a teacher/kiai in producing students with character or noble character.  The role of Islamic boarding school  in character education is that Islamic boarding school  must play themselves as guardians and preservers of religious values; Islamic boarding school  as educational institutions, of course, are also required to play themselves as reformers of religious understanding; and as religious education institutions and socio-community education, Islamic boarding school  can also carry out their roles, duties, missions, and functions as inspirers, motivators, and dynamists of development implementation at the local and regional levels in their respective regions.